The Development of Curriculum in Homeschooling of Primagama Serang - Vidiana Rahmat (Journal of English Language Teaching and Cultural Studies, 2019)
This research is aimed to get deep understanding about the development Curriculum in Homeschooling of Primagama Serang. The research uses qualitative research with case study as the method. Subjects of research are principals, academic staff, teacher, and students of Homeschooling Primagama Serang. Data collecting technique for this research are observation, interview, and documentation. The result of research shows that Homeschooling of Primagama Serang has run its curriculum which integrated to 2013 Curriculum. This school has also improved the competence of the teachers about 2013 curriculum, and facilitates them with the sophisticated learning media.